Innovative Educational Game: Designing and Developing Interactive Web-Based Memory Card Games as an Educational Media for Children - Nurul Helda; Sanusi Sanusi; Rivansyah Suhendra (Yayasan Adra Karima Hubbi, 2023)
In the dynamic landscape of children’s education, innovation plays a pivotal role in shaping engaging and effective learning experiences. This research focuses on the design and development of an interactive web-based memory card game as an innovative educational tool. Grounded in the waterfall method, the development process prioritizes sequential stages to ensure robustness. Performance testing, using PageSpeed Insights, evaluates the game’s speed and efficiency, aiming to enhance user experience. The results, showcased by a remarkable score of 99, affirm the careful consideration given to optimization techniques. This research not only contributes to the broader understanding of game-based learning but also provides concrete insights for developers. The memory card game stands as a testament to the seamless integration of technological innovations into children’s education, promising enduring contributions to the future of learning.